Assessing the costs of industrial decarbonization - Gunther Glenk; Rebecca Maier; Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Companies in various industries are under growing pressure to assess the costs of decarbonizing their operations. This paper develops a generic abatement cost concept to identify the cost-efficient combination of technological and operational changes firms would need to implement to drastically reduce greenhouse gas emissions from current production processes. The abatement cost curves resulting from our framework further serve as a decision tool for managers to determine the optimal abatement levels in the presence of environmental regulations, such as carbon pricing. We calibrate our model in the context of uropean cement producers that must obtain emission permits under the European Emission Trading System (EU ETS). We find that a price of exteuro85 per ton of carbon dioxide (CO2), as observed on average in 2023 under the EU ETS, incentivizes firms to reduce their annual direct emissions by about one-third relative to the status quo. Yet, this willingness to abate emissions increases sharply if carbon prices were to rise above the exteuro100 per ton of CO2 benchmark.
Keywords: M1; O33; Q42; Q52; Q54; Q55; Q58; 330; marginal abatement cost; carbon emissions; industrial decarbonization; cement production